Dampak Ketersediaan Laporan Keuangan Pada Perencanaan Usaha UMKM Serta Model Pelaporan Keuangan Berbasis SAK EMKM - Nurlinda, Nurlinda; Asmalidar, Asmalidar; Riswanto, Riswanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The purpose of this study is to determine the relationship between the availability of financial reports and planning in MSMEs and to design a simple financial report preparation processing model for Micro, Small, and Medium Enterprises (MSMEs), as well as to provide practical recommendations regarding financial report models that can be immediately implemented for MSME business planning so that business continuity can be maintained. This study is a quantitative and quantitative study using primary and secondary data collected through questionnaires, interviews, observations and documentation of 13 respondents of MSMEs assisted by Dharma Wanita of Politeknik Negeri Medan. Data were analyzed using product moment and descriptive analysis. The results of this study indicate that there is a strong relationship between the availability of financial reports and MSME planning of 0.979 in the range of 0.80-1.000 (Very Strong). The MSME Financial Report Model using the MSME SAK Standard is adequate for MSME financial management. The application of financial reports in MSME planning involves utilizing information sourced from the financial reports to develop business plans, including sales, production, capital, and profit planning.